(3n-4)(5n+2)=0

Simple and best practice solution for (3n-4)(5n+2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3n-4)(5n+2)=0 equation:


Simplifying
(3n + -4)(5n + 2) = 0

Reorder the terms:
(-4 + 3n)(5n + 2) = 0

Reorder the terms:
(-4 + 3n)(2 + 5n) = 0

Multiply (-4 + 3n) * (2 + 5n)
(-4(2 + 5n) + 3n * (2 + 5n)) = 0
((2 * -4 + 5n * -4) + 3n * (2 + 5n)) = 0
((-8 + -20n) + 3n * (2 + 5n)) = 0
(-8 + -20n + (2 * 3n + 5n * 3n)) = 0
(-8 + -20n + (6n + 15n2)) = 0

Combine like terms: -20n + 6n = -14n
(-8 + -14n + 15n2) = 0

Solving
-8 + -14n + 15n2 = 0

Solving for variable 'n'.

Factor a trinomial.
(-2 + -5n)(4 + -3n) = 0

Subproblem 1

Set the factor '(-2 + -5n)' equal to zero and attempt to solve: Simplifying -2 + -5n = 0 Solving -2 + -5n = 0 Move all terms containing n to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -5n = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -5n = 0 + 2 -5n = 0 + 2 Combine like terms: 0 + 2 = 2 -5n = 2 Divide each side by '-5'. n = -0.4 Simplifying n = -0.4

Subproblem 2

Set the factor '(4 + -3n)' equal to zero and attempt to solve: Simplifying 4 + -3n = 0 Solving 4 + -3n = 0 Move all terms containing n to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3n = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3n = 0 + -4 -3n = 0 + -4 Combine like terms: 0 + -4 = -4 -3n = -4 Divide each side by '-3'. n = 1.333333333 Simplifying n = 1.333333333

Solution

n = {-0.4, 1.333333333}

See similar equations:

| y=-x^2+14x-45 | | 5.99+1.99x=20.99 | | 11.3x+7=4.6x+22.41 | | -5.6=y | | (3-i)-(2+6i)= | | 8x+3-7=12 | | Y-1=2(x-3/2) | | 2.6x+78=5.1x+18 | | 7x=9x-9 | | 4+6x=7x-7 | | 5x+9=10x-7 | | 5(x+4)-x=32 | | (4a+3)(a-1)=0 | | 18y=29x-52 | | -16.28=29.3-8.6y | | Y-1=2(x-2/3) | | 3x-(9x+5)=2x-37 | | 8m-20=12+6m | | 8.4y+9.77=-62.47 | | -21.32=3.2x+3 | | 3b^2-2=25 | | 8t+6-7t=6 | | 4x-30=7x-54 | | 6.6+1.7n=2.52 | | 5(2-4r)-3r=4r-287 | | 1.01(1.27)(9-x)=11 | | 4b=2b-1 | | 5.5y-6.1=19.20 | | b=3/4 | | 24(1.5+3)=n | | 8z(squared)=6z(squared)+38 | | x+27.3=8.9 |

Equations solver categories